Effects of aging on cognitive and brain inter-network integration patterns underlying usual and dual-task gait performance - Droby, Amgad; Varangis, Eleanna; Habeck, Christian; Hausdorff, Jeffrey M.; Stern, Yaakov; Mirelman, Anat; Maidan, Inbal (Frontiers in Aging Neuroscience, 2022)
Introduction: Aging affects the interplay between cognition and gait performance. Neuroimaging studies reported associations between gait performance and structural measures; however, functional connectivity (FC) analysis of imaging data can help to identify dynamic neural mechanisms underlying optimal performance. Here, we investigated the effects on divergent cognitive and inter-network FC patterns underlying gait performance during usual (UW) and dual-task (DT) walking. Methods: 115 community-dwelling, healthy participants between 20-80 years were enrolled. All participants underwent comprehensive cognitive and gait assessments in two conditions and resting state functional MRI scans. Inter-network FC from motor-related to 6 primary cognitive networks was estimated. Step-wise regression models tested the relationships between gait parameters, inter-network FC, neuropsychological scores, and demographic variables. A threshold of p<0.05 was adopted for all statistical analyses. Results: UW was largely associated with FC levels between motor and sustained attention networks. DT performance was associated with inter-network FC between motor and divided attention, and processing speed in the overall group. In young adults, UW was associated with inter-network FC between motor and sustained attention networks. On the other hand, DT performance was associated with cognitive performance, as well as inter-network connectivity between motor and divided attention networks (VAN and SAL). On the other hand, the older age group (> 65 years) showed increased integration between motor, dorsal, and ventral attention, as well as default-mode networks, was negatively associated with UW gait performance. Inverse associations between motor and sustained attention inter-network connectivity and DT performance was observed. Conclusions: While UW relies on inter-network FC between motor and sustained attention networks, DT performance relies on additional cognitive capacities, increased motor, and executive control network integration. FC analyses demonstrate that the decline in cognitive performance with aging leads to the reliance on additional neural resources required maintaining routine walking tasks.